Provenance of Inorganic Carbon Sinks in Closed Basins. Issue 3 (16th March 2022) - Li, Yu; Hao, Lu; Han, Qin; Zhang, Yuxin; Peng, Simin; Zhang, Xinzhong
Abstract: Much dissolved inorganic carbon (DIC) may exist in lacustrine carbonates in the terminal lakes of closed basins in arid areas, and inorganic carbon sinks in arid regions are an important hypothesis of global carbon cycle research in recent years. Previous studies have made significant progress in estimating the inorganic carbon content. However, the source of inorganic carbon sinks remains unclear. Here, we choose four typical arid closed basins in North China to investigate the provenance of inorganic carbon sinks. The results show that CO2 absorbed by saline‐alkaline soil is the main source of groundwater DIC in the study area, with a contribution rate of approximately 50%. Forty‐three groundwater radiocarbon ages from arid closed basins indicate that the DIC in groundwater is transported along the direction of water flow and deposited in terminal lakes, forming inorganic carbon sinks. Our study suggests that the total inorganic carbon contents of Zhuye Lake, Yanchi Lake, Huahai Lake, and Qinghai Lake in the Holocene are 0.318 Pg, 0.003 Pg, 0.160 Pg, and 3.289 Pg, respectively. The results demonstrate that inorganic carbon sinks are much larger than lake organic carbon storage, thereby serving as an important carbon cycle factor in arid regions. Plain Language Summary: As observation methods and experimental technologies have advanced, research on the global carbon cycle has penetrated all links of the Earth's surface system. The long‐neglected arid zone ecosystem exerts a significant impact on the interannual changes in global terrestrial carbon sinks. Despite this, research on the source of inorganic carbon sinks in arid areas is still insufficient. Therefore, age measurements and isotopic analyses are conducted in groundwater, river water and sediments in four arid closed basins of North China, and the main sources of inorganic carbon sinks in arid closed basins are explored. The results show that groundwater dissolved inorganic carbon is mainly derived from the CO2 absorbed by the saline‐alkaline soil through river leakage and irrigation and finally reaches the terminal lakes. Taken together, soil CO2 is one of the leading sources of inorganic carbon sinks in closed basins. Key Points: CO2 absorbed by saline‐alkaline soil is the main source of groundwater dissolved inorganic carbon (DIC) with a contribution rate of about 50% The DIC formed by the carbon absorption of saline‐alkaline soils becomes an inorganic carbon sink The rate of Holocene inorganic carbon sinks from lacustrine carbonates is much higher than that of organic carbon accumulation